Android-Based Education toward the Role of Postpartum Primipara Mothers in Fulfilling the Independent Perinium Care - Werna Nontji; Dwi Kartika Sari; Sitti Maria Ulfa; Syafruddin Syarif; Inez Vravty Lestari; Nunung Aryiany; Ummul Khaer; Hasniah Hasniah; Herawati Herawati; Sumarni Syam (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: Educating mothers during their postpartum period could potentially help them to overcome some important phases after giving birth. The process of education is evaluated based on the mothers’ knowledge about their independent self-care. Independency is an activity that is started individually and is done based on self-capability. The independency in the postpartum care is not only important to decrease the mother’s mortality and morbidity rate, but it is also crucial to strengthen and improve the post-partum mother’s healthy behavior during the perineal care. Providing education using Android-based application called BUBI Care could be potential to facilitate a more dynamic transfer of knowledge to the postpartum mothers.Aims: To analyze the knowledge, skills, and independence of primipara postpartum mothers in independent perineal care before and after accessing BUBI Care app. Research Method: employing quasi experimental research with pre-test and post-test design with control group design. The sample for this research were 19 pregnant mothers TM III (pregnancy age of ? 38 weeks) on each group. The treatment group was educated using BUBI Care Android app that was conducted at one of Public Health Center. The control group was educated without BUBI Care that was conducted at a Midwife Practice Clinic. The research was conducted on September to October 2020. Study Result: According to the Wilcoxon test, there was a difference in the pre-test knowledge of the treatment and control groups with the similar median of 53 and p-value of 0.666, the treatment group showed their scores improved to 80 on the post-test while the control group stayed at 53 with the p-value of 0.000. It means that BUBI Care app education influences the post-test. On the other hand, the perineal care skill saw a difference between the intervention and control groups. The intervention group had a mean of 70.05 and 56.68 for the control group with the p-value of 0.002 which means that there was an influence from the BUBI Care app education. Additionally, Mann Whitney test showed that the intervention group had a mean score of 78.95, but the control group only had 49.26, the total difference between the two are 29.69 with the p-value of 0.000. It can be concluded that there is a significance in difference in the independency rate from the provision of BUBI Care Android app education.Conclusion: there is a significance effect on the intervention group in terms of Android based usage.